IN VOLO SUL TEVERE DA STIMIGLIANO A PONTE DEL GRILLO: “IL RITRATTO DEL TERRENO” DAL PALLONE (1908) (GEOmedia, 2022)
The paper describes time, modes and techniques of realization in 1908 of a photomosaic, from balloon, of a section of the course of the Tiber river. The photomosaic was carried out by the Brigata Mista Specialisti of Genio Militare headed by Captain Cesare Tardivo, on order of the Genio Civile, as part of a navigation project of the Tiber river from the sea to Orte. The pioneering photomosaic, regarding the 50 km section from Ponte del Grillo to Stimigliano, is kept at the photographic archive of the Aerofototeca Nazionale - ICCD, and it is the first application of the new tecnique called topophotograpy in the civil field: presented as the "true portrait of the terrain" at the main international conferences of the time, earned Italy an undisputed leading place in the field of aerial photography and photogrammetry.